O que os outros não veem - Queiroz, Stéfanie, Bellomi (2021)
The work presents a confection of artistic make-up, props and photographs based on the question: “What are you that others don't see, but would you like to be seen?”. In this way, through the concepts of Relational Art and the “bodymedia” Theory, two photographic series were created that express a dive into the reality of the “other”. Thus, the intention was to express the theme through self-portraits and explore the relationship between artistic makeup and the production of props for the composition of photographs, consisting of a contemporary and poetic vein of expression, which could generate questions and reflections on resilience, identity, empathy, and different interpretations of reality through known narratives.